A facile and mild strategy to fabricate an underwater superoleophobic and underoil superhydrophobic mesh with outstanding anti-viscous oil-fouling properties for switchable high viscosity oil/water separation. Issue 18 (27th August 2019) - Zhang, Jin; Zhang, Lu; Zhao, Jianguo; Qu, Wenshan; Wang, Zhenxing
Abstract : Underwater superoleophobic and underoil superhydrophobic mesh has been prepared for switchable high viscosity oil/water separation. Abstract : Underwater superoleophobic and underoil superhydrophobic materials have distinct advantages for switchable oil–water separation. Although some strategies have been developed to fabricate these materials, harsh conditions such as high temperature and pressure, abundant harmful organic solvents and complicated devices are usually needed, limiting their practical applications. Moreover, due to the high adhesion properties of some oils such as crude oil, the anti-viscous oil-fouling performance of usual superwetting material is still unsatisfactory. Herein, based on the corrosion process and mussel-inspired surface coating, we have developed a mild and eco-friendly route to transform iron meshes into underwater superoleophobic and underoil superhydrophobic materials for switchable high viscosity oil–water separation. The corrosion process can generate microsphere-nanosheet structures (MNS) composed of microspheres and abundant nanosheet arrays on the iron mesh surface, while the subsequent mussel-inspired surface coating can form a compact layer to protect the MNS from damage, finally endowing the resultant mesh with durable underwater superoleophobicity and underoil superhydrophobicity. Significantly, the resultant mesh exhibits excellent anti-crude oil-fouling properties, and can separate various oil–water mixtures with high efficiency (all above 98%). Moreover, after immersion in acidic or basic solutions, the wetting properties of the mesh showed no apparent variation, demonstrating that the mesh possesses a desirable environmental stability. According to the dual superlyophobic properties of the as-prepared mesh in water–oil systems, a dual-channel device has been designed to realize the continuous separation of the crude oil–water mixture with high efficiency (above 93% after 30 cycles). This strategy may open a new avenue to prepare high-performance separation materials for viscosity oil–water separation.